The Cross-Talk Between the Peripheral and Brain Cholesterol Metabolisms - Ilinca Savulescu-Fiedler; Luiza-Roxana Dorobantu-Lungu; Serban Dragosloveanu; Serban Nicolae Benea; Christiana Diana Maria Dragosloveanu; Ana Caruntu; Andreea-Elena Scheau; Constantin Caruntu; Cristian Scheau (Current Issues in Molecular Biology)
Cholesterol is an essential element for the development and normal function of the central nervous system. While peripheral cholesterol is influenced by liver metabolism and diet, brain cholesterol metabolism takes place in an isolated system due to the impermeability of the blood–brain barrier (BBB). However, cross-talk occurs between the brain and periphery, specifically through metabolites such as oxysterols that play key roles in regulating cholesterol balance. Several neurodegenerative conditions such as Alzheimer’s disease or Parkinson’s disease are considered to be affected by the loss of this balance. Also, the treatment of hypercholesterolemia needs to consider these discrete interferences between brain and peripheral cholesterol and the possible implications of each therapeutic approach. This is particularly important because of 27-hydroxycholesterol and 24-hydroxycholesterol, which can cross the BBB and are involved in cholesterol metabolism. This paper examines the metabolic pathways of cholesterol metabolism in the brain and periphery and focuses on the complex cross-talk between these metabolisms. Also, we emphasize the regulatory role of the BBB and the need for an integrated approach to cholesterol management.